AACVD synthesis of catalytic gold nanoparticle‐modified cerium(IV) oxide thin films. Issue 7 (5th June 2015) - Evans, Meghan; Di Maggio, Francesco; Blackman, Chris; Sankar, Gopinathan; Hoffmann, Patrik; Knez, Mato; Vahlas, Constantin; Alexandrov, Sergei
Abstract Co‐deposition of Ce(dbm)4 and NH4AuCl4 precursors in acetone at 500 °C via AACVD results in deposition of crystalline CeO2 thin films containing/decorated with metallic gold. These particles are estimated to be ∼ 70 nm in size via optical methods. Preliminary testing of catalytic activity showed the materials were surprisingly catalytically active given the very small amounts of gold present and the large estimated particle size, although the presence of smaller catalytically active particles could not be discounted. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)